2021
DOI: 10.3390/vetsci8070129
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cardiovascular Tolerance to Hemorrhage after Oral Resveratrol Pretreatment in Dogs

Abstract: Resveratrol has been shown to preserve organ function and improve survival in hemorrhagic shock rat models. This study investigated whether seven days of oral resveratrol could improve hemodynamic response to hemorrhage and confer benefits on risk of acute kidney injury (AKI) without inducing coagulopathy in a canine model. Twelve greyhound dogs were randomly allocated to receive oral resveratrol (1000 mg/day) or placebo for seven days prior to inducing hemorrhage until a targeted mean blood pressure of ≤40 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Light microscopy features may include dilation of PT lumens, flattening of epithelium, vacuolization, simplification, and loss of brush border (which provides the large surface area needed for reabsorption of nutrients and electrolytes normally) (Fig. 1) [13]. Similarly, PT electronic microscopy demonstrates the loss of brush border cells in association with subtle but notable changes, including mitochondrial swelling and fragmentation (Fig.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Light microscopy features may include dilation of PT lumens, flattening of epithelium, vacuolization, simplification, and loss of brush border (which provides the large surface area needed for reabsorption of nutrients and electrolytes normally) (Fig. 1) [13]. Similarly, PT electronic microscopy demonstrates the loss of brush border cells in association with subtle but notable changes, including mitochondrial swelling and fragmentation (Fig.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…Bar is 2 μm. This figure is reproduced with permission from the publisher of reference [13]. EM, electron micrograph.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…Davis et al [ 8 ] demonstrated that resveratrol treatment did not appear to induce an increased bleeding risk and could improve greyhound dogs’ blood pressure tolerance to severe hemorrhage. Despite this, they did not observe the kidney-protective effects of resveratrol.…”
mentioning
confidence: 99%